Influence of the order of the physical qualities during the microcycle on the weekly external loads and match day`s readiness level in highly trained academy soccer players - Douchet, T.; Paizis, C.; Babault, N. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Highly trained academy soccer practitioners usually implement an aerobic-oriented session followed by a speed-oriented session during the first and second heavy load session of a training week, respectively. This study aimed to investigate if the order of these physical training sessions would influence the external training loads and the subsequent readiness level on match day. METHODS: Twenty-five highly trained academy soccer players (12 U17 and 13 U19) participated in two experimental weeks randomly presented. The AEROBIC-SPEED periodization implemented an aerobic-oriented session on MD-4 and a speed-oriented session on MD-2. The SPEED-AEROBIC periodization did the opposite. During these two sessions, players wore a global positioning system and rated their perceived exertion (RPE). Players were also tested on MD-4 for baseline values (CONTROL) and match-day (TEST). Tests included a counter movement jump (CMJ), a 20-m sprint, the Illinois agility test (IAT), and the Hooper questionnaire. RESULTS: For the aerobic-oriented session, players reported greater distances during AEROBIC-SPEED periodization than SPEED-AEROBIC in 15-20 km/h (1273.53±328.51 m vs. 1174.84±210.33 m, P<0.05) and 20-25 km/h (658.92±264.41 m vs. 478.17±259.10 m, P<0.01). For the speed-oriented session, players reported greater distances during SPEED-AEROBIC than AEROBIC-SPEED periodization in 20-25 km/h (298.84±120.12 m vs. 223.24±114.86 m, P<0.05) and >25 km/h (110.74±34.65 m vs. 84.96±43.85 m, P<0.05). Tests revealed similar values for CONTROL and TEST between the two experimental weeks for CMJ, 20m, IAT and Hooper. CONCLUSIONS: The physical qualities (both aerobic and speed), when periodized at the beginning of the week (on MD-4) rather than later (MD-2) showed higher external loads without changing the readiness level on MD. The results emphasize the need to periodize the training contents according to the aim of the cycle.